Conservative treatment of a scoliosis patient after two heart surgeries in early childhood - A case report - Hans-Rudolf Weiss; Manuel Lay; Tamisha Best-Gittens; Marc Moramarco; Mario Jimeranez (AOSIS, 2021)
Introduction: This is a case report of a juvenile female patient with scoliosis following two heart surgeries for congenital heart disease (CHD). Patient presentation, management and outcome: Initially, the premenarchial female was 9 years old and had a Tanner stage 2-3 with a single thoracic curve of 65° Cobb. Because of the high risk for progression, immediate brace treatment was proposed as the father declined surgery. The patient received intensive treatment according to the Schroth Best Practice® programme and a Gensingen Brace® designed for large thoracic curves. Over the 18 months following the initial visit, she received two additional braces. As a result, the progression of the main curve was prevented. The patient continues to maintain an improved cosmetic result and is currently at a Risser 2. Conclusion: Surgery performed for CHD in rare cases may lead to stiff spinal deformity as a consequence of that surgery. Progression of a severe and stiff curve was prevented during the most vulnerable phase of the pubertal growth spurt with an improved clinical result. Therefore, we assume that the patient may have a normal life in adulthood with minor restrictions only. Supported by pattern-specific high correction exercises and braces, these typical single thoracic curves can be re-compensated to a more balanced appearance, less prone to progression in adulthood. Clinical implications: Because of the relative high risks of spinal fusion and the long-term unknowns of such an intervention, high-impact conservative treatment should be implemented first before surgical correction is considered.